Motility response to colonic distention is increased in postinfectious irritable bowel syndrome (PI‐IBS). Issue 5 (13th February 2014) - Kanazawa, M.; Palsson, O. S.; van, M. A. L.; Gangarosa, L. M.; Fukudo, S.; Whitehead, W. E.
Abstract Background Acute intestinal infection leads to persistent intestinal smooth muscle hypercontractility and pain hypersensitivity after resolution of the infection in animal models. We investigated whether postinfectious irritable bowel syndrome (PI‐IBS) is associated with abnormalities in phasic contractions of the colon, smooth muscle tone, and pain sensitivity compared to non‐PI‐IBS (NI‐IBS) or healthy controls (HC). Methods Two hundred and eighteen Rome III‐positive IBS patients and 43 HC participated. IBS patients were designated PI‐IBS, if their IBS symptoms began following an episode of gastroenteritis characterized by two or more of: fever, vomiting, or diarrhea. Pain threshold to phasic distentions of the descending colon was assessed using a barostat. Colonic motility was assessed with the barostat bag minimally inflated to the individual operating pressure (IOP), at 20 mmHg above the IOP, and following a test meal. IBS symptom severity and psychological symptoms were assessed by the IBS Severity Scale (IBS‐SS) and the Brief Symptom Inventory‐18 (BSI‐18). Key Results Twenty two (10.1%) met criteria for PI‐IBS. Both IBS and HC groups showed a significant increase in motility index during intraluminal distention and following meals. The magnitude of the response to distention above (orad to) the balloon was significantly greater in PI‐IBS compared with NI‐IBS (p < 0.05) or HC (p < 0.01). Differences between PI‐IBS and NI‐IBS were not significant for IBS symptom severity, pain threshold, barostat bag volumes, or any psychological score on the BSI‐18. Conclusions & Inferences Patients with PI‐IBS have greater colonic hypercontractility than NI‐IBS. We speculate that sustained mild mucosal inflammation may cause this colonic irritability.